A Tandem Duplicate of Anti-Müllerian Hormone with a Missense SNP on the Y Chromosome Is Essential for Male Sex Determination in Nile Tilapia, Oreochromis niloticus - Li, Minghui; Sun, Yunlv; Zhao, Jiue; Shi, Hongjuan; Zeng, Sheng; Ye, Kai; Jiang, Dongneng; Zhou, Linyan; Sun, Lina; Tao, Wenjing; Nagahama, Yoshitaka; Kocher, Thomas D.; et al. (PLoS genetics, 2015)
Variation in the TGF-β signaling pathway is emerging as an important mechanism by which gonadal sex determination is controlled in teleosts. Here we show that amhy, a Y-specific duplicate of the anti-Müllerian hormone (amh) gene, induces male sex determination in Nile tilapia. amhy is a tandem duplicate located immediately downstream of amhΔ-y on the Y chromosome. The coding sequence of amhy was identical to the X-linked amh (amh) except a missense SNP (C/T) which changes an amino acid (Ser/Leu92) in the N-terminal region. amhy lacks 5608 bp of promoter sequence that is found in the X-linked amh homolog. The amhΔ-y contains several insertions and deletions in the promoter region, and even a 5 bp insertion in exonVI that results in a premature stop codon and thus a truncated protein product lacking the TGF-β binding domain. Both amhy and amhΔ-y expression is restricted to XY gonads from 5 days after hatching (dah) onwards. CRISPR/Cas9 knockout of amhy in XY fish resulted in male to female sex reversal, while mutation of amhΔ-y alone could not. In contrast, overexpression of Amhy in XX fish, using a fosmid transgene that carries the amhy/amhΔ-y haplotype or a vector containing amhy ORF under the control of CMV promoter, resulted in female to male sex reversal, while overexpression of AmhΔ-y alone in XX fish could not. Knockout of the anti-Müllerian hormone receptor type II (amhrII) in XY fish also resulted in 100% complete male to female sex reversal. Taken together, these results strongly suggest that the duplicated amhy with a missense SNP is the candidate sex determining gene and amhy/amhrII signal is essential for male sex determination in Nile tilapia. These findings highlight the conserved roles of TGF-β signaling pathway in fish sex determination.